2017
DOI: 10.1007/s00127-017-1371-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the risk of crime and victimisation in people with intellectual disability: a data-linkage study

Abstract: PWID are at increased risk of victimisation and perpetration of violent and sexual crimes. Risk of sex offending and victimisation is particularly elevated, and signalling the need for specialised interventions to prevent offending and to ensure victims is assisted with access to justice, support, and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
1
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 42 publications
7
49
1
8
Order By: Relevance
“…However, these gender-based differences were not statistically significant, as indicated by the overlapping confidence intervals. Of note, the rates of crime reported for this sample, both for those with and without comorbid mental illness, were significantly higher than those reported among community comparisons sample of people without intellectual disability (Fodgen et al, 2016;Nixon et al, 2017), indicating a statistically significant association between being charged with a criminal offence and having an intellectual disability. While the reasons for this increased statistical likelihood are not able to be discerned from these data, the results add to the argument regarding the need for more focus on providing a greater range of cross-agency supports and interventions from health, disability and justice services that better meet the increased range and complexity of needs presented by those with dual disability who offend, both in institutions and community settings (Fazel et al, 2008;Simpson et al, 2001).…”
Section: Dual Disability and Criminalitycontrasting
confidence: 57%
See 2 more Smart Citations
“…However, these gender-based differences were not statistically significant, as indicated by the overlapping confidence intervals. Of note, the rates of crime reported for this sample, both for those with and without comorbid mental illness, were significantly higher than those reported among community comparisons sample of people without intellectual disability (Fodgen et al, 2016;Nixon et al, 2017), indicating a statistically significant association between being charged with a criminal offence and having an intellectual disability. While the reasons for this increased statistical likelihood are not able to be discerned from these data, the results add to the argument regarding the need for more focus on providing a greater range of cross-agency supports and interventions from health, disability and justice services that better meet the increased range and complexity of needs presented by those with dual disability who offend, both in institutions and community settings (Fazel et al, 2008;Simpson et al, 2001).…”
Section: Dual Disability and Criminalitycontrasting
confidence: 57%
“…Glaser and Florio () highlighted the complex and ongoing needs of offenders who have a dual disability, commenting that the presence of a comorbid mental illness may contribute to “behaviours and difficulties that lead to offending by an intellectually disabled person.” This is supported by results of a study by Vanny, Levy, Greenberg, and Hayes () who reported that just under half of a sample of 60 individuals presenting to Magistrates Court, in New South Wales, Australia, with an intellectual disability also reported having a mental illness. Furthermore, two recent epidemiological studies from Australia have reported that people with an intellectual disability and a mental illness had an increased likelihood of being charged with criminal offences, compared to those with intellectual disability but no mental illness, and to people in the general community (Fodgen, Thomas, Daffern, & Ogloff, ; Nixon, Thomas, Daffern, & Ogloff, ). Based on the available research findings, suggesting the increased risks of perpetrating crime and the heightened rates of mental illness reported across studies, Simpson and colleagues (Simpson, Martin, & Green, ) suggested that people with dual disability who come into contact with the criminal justice system represent a “triply stigmatized” group, attracting the labels of “criminal,” “disabled” and “psychiatric,” and experience inequities in access to appropriate services, especially when cross‐agency responses are indicated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are similar to those of other studies in the field; Van Den Bergh and Hoekman (2006) found that the majority of victims in their study were female in their twenties who were alleged victims of sexual abuse. PWID's vulnerability to being sexually exploited regardless of gender was also reported by Nixon et al (2017).…”
Section: Discussionmentioning
confidence: 95%
“…People with disabilities, such as intellectual disabilities (PWID) and autism (PWA), are more exposed to physical and sexual abuse than the general population (Mandell et al 2005;Hershkowitz et al 2007;Hughes et al 2012;Jones et al 2012;Nixon et al 2017). PWID are characterised by deficits in intellectual functioning, social and adaptive domains such as language comprehension, memory skills and weaker comprehension of social demands (World Health Organization 2019).…”
mentioning
confidence: 99%